The use of temozolomide in paediatric metastatic phaeochromocytoma/paraganglioma: A case report and literature review - Urquhart, Calum; Fleming, Ben; Harper, Ines; Aloj, Luigi; Armstrong, Ruth; Hook, Liz; Long, Anna-May; Jackson, Claire; Gallagher, Ferdia A.; McLean, Mary A.; Tarpey, Patrick; Kosmoliaptsis, Vasilis; et al. (Frontiers in Endocrinology, 2022)
There is increasing evidence to support the use of temozolomide therapy for the treatment of metastatic phaeochromocytoma/paraganglioma (PPGL) in adults, particularly in patients with SDHx mutations. In children however, very little data is available. In this report, we present the case of a 12-year-old female with a SDHB-related metastatic paraganglioma treated with surgery followed by temozolomide therapy. The patient presented with symptoms of palpitations, sweating, flushing and hypertension and was diagnosed with a paraganglioma. The primary mass was surgically resected six weeks later after appropriate alpha- and beta-blockade. During the surgery extensive nodal disease was identified that had been masked by the larger paraganglioma. Histological review confirmed a diagnosis of a metastatic SDHB-deficient paraganglioma with nodal involvement. Post-operatively, these nodal lesions demonstrated tracer uptake on 18F-FDG PET-CT. Due to poor tumour tracer uptake on 68Ga-DOTATATE and 123I-MIBG functional imaging studies radionuclide therapy was not undertaken as a potential therapeutic option for this patient. Due to the low tumour burden and lack of clinical symptoms, the multi-disciplinary team opted for close surveillance for the first year, during which time the patient continued to thrive and progress through puberty. 13 months after surgery, evidence of radiological and biochemical progression prompted the decision to start systemic monotherapy using temozolomide. The patient has now completed ten cycles of therapy with limited adverse effects and has benefited from a partial radiological and biochemical response.